EKSPLORASI KONTEN TIKTOK TERHADAP MINAT WISATA MENURUT GENERASI Z - Mustika, Wida; Kusuma, Pradana Jati; Anomsari, Ariati; Puspitasari, Diana (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the influence of content quality and storytelling on the travel interest of Generation Z on the social media platform TikTok, with perceived value (emotional, functional, and social) as a mediation. The research method used is quantitative, employing Structural Equation Modeling (SEM) through SmartPLS. Data were collected from 176 respondents who are active TikTok users, engaging with the platform 1-3 times a week. The results of the study indicate that (1) storytelling has a significant positive effect on travel interest; (2) content quality has a non-significant effect on travel interest; (3) storytelling has a significant positive effect on perceived emotional, functional, and social value; (4) perceived emotional and social values have a non-significant effect on travel interest, while perceived functional value has a significant positive effect on travel interest; (5) perceived emotional and social values do not mediate the influence of storytelling on travel interest, whereas perceived functional value does mediate the influence of storytelling on travel interest. This research provides important insights for tourism destination managers in designing effective marketing strategies to attract the attention of Generation Z. Future research should explore storytelling on other digital platforms, explore the factors that influence travel interest with a focus on the functional value of destinations, and adapt content to Generation Z's preference for concise and authentic information.